Applied Cryptography and Network Security 13th International Conference, ACNS 2015, New York, NY, USA, June 2-5, 2015, Revised Selected Papers - Malkin, Tal.; Kolesnikov, Vladimir; Lewko, Allison Bishop; Polychronakis, Michalis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 13th International Conference on Applied Cryptography and Network Security, ACNS 2015, held in New York, NY, USA, in June 2015. The 33 revised full papers included in this volume and presented together with 2 abstracts of invited talks, were carefully reviewed and selected from 157 submissions. They are organized in topical sections on secure computation: primitives and new models; public key cryptographic primitives; secure computation II: applications; anonymity and related applications; cryptanalysis and attacks (symmetric crypto); privacy and policy enforcement; authentication via eye tracking and proofs of proximity; malware analysis and side channel attacks; side channel countermeasures and tamper resistance/PUFs; and leakage resilience and pseudorandomness.
Secure computation: primitives and new models -- Public key cryptographic primitives -- Secure computation II: applications -- Anonymity and related applications -- Cryptanalysis and attacks (symmetric crypto) -- Privacy and policy enforcement -- Authentication via eye tracking and proofs of proximity -- Malware analysis and side channel attacks -- Side channel countermeasures and tamper resistance/PUFs -- Leakage resilience and pseudorandomness.
Keywords: Computer science; Computer communication systems; Computer security; Data encryption (Computer science).; Computers; Computers and civilization; Management information systems; Computer Science; Systems and Data Security; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Theory of Computation; Computers and Society; Electronic books